2019
DOI: 10.1002/adfm.201905213
|View full text |Cite
|
Sign up to set email alerts
|

Transformable Nanoparticle‐Enabled Synergistic Elicitation and Promotion of Immunogenic Cell Death for Triple‐Negative Breast Cancer Immunotherapy

Abstract: Although cisplatin‐based neoadjuvant chemotherapy is an efficient therapy approach for triple‐negative breast cancer (TNBC), it has dismal prognosis and modestly improved survival benefit. Here, a synergistic immunotherapy of TNBC premised on the elicitation and promotion of immunogenic cell death (ICD) response, through a transformable nanoparticle‐enabled approach for contemporaneous delivery of cisplatin, adjudin, and WKYMVm is reported. The nanoparticles can sequentially respond to matrix metalloproteinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 68 publications
1
38
0
Order By: Relevance
“…A multi stimuli-responsive peptide-based prodrug with structure-transformable characteristics for simultaneous delivery of Pt, adjudin (ADD), and WKYMVm was constructed by Xu et al as a combination of chemo- and immunotherapy [ 73 ]. This SDDS responded well to matrix metalloproteinase-2 (MMP-2), a weakly acidic pH, and glutathione (GSH) to achieve structural transformation with the advantages of efficient and sustained drug delivery.…”
Section: Bio-inspired Tumor-homing Nanosystems For Tnbc Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A multi stimuli-responsive peptide-based prodrug with structure-transformable characteristics for simultaneous delivery of Pt, adjudin (ADD), and WKYMVm was constructed by Xu et al as a combination of chemo- and immunotherapy [ 73 ]. This SDDS responded well to matrix metalloproteinase-2 (MMP-2), a weakly acidic pH, and glutathione (GSH) to achieve structural transformation with the advantages of efficient and sustained drug delivery.…”
Section: Bio-inspired Tumor-homing Nanosystems For Tnbc Treatmentmentioning
confidence: 99%
“…Enhanced expression of activated caspase-3 (cas-3), as well as the elevated release of TNF-α and interferon gamma (INF-γ), were documented in response to 3-NPs. In addition, it was observed that mice treated with 3-NPs had a lower amount of vascular endothelial growth factor (VEGF)-positive cells aside from the reduced levels of CD31 and MMP-9, demonstrating the potency of 3-NPs on the adaptive and innate immune system against TNBC and its metastasis [ 73 ]. A similar structural transformability, prolonged retention, and higher tumor accumulation have been shown between 3-NPs and 2-NPs.…”
Section: Bio-inspired Tumor-homing Nanosystems For Tnbc Treatmentmentioning
confidence: 99%
“…In another case, Zhang et al reported an immunotherapy strategy for triple-negative breast cancer based on enzyme-responsive and structure-transformable nanoparticles, as illustrated in Figure 4A (Xu et al, 2019 ). Firstly, peptides containing anti-tumor agents cisplatin (Pt) and adjudin (ADD) and MMP-2-recognizable sequences were synthesized and then self-assembled into spherical nanoparticles with diameters less than 100 nm.…”
Section: Enzyme-responsive Nanoparticlesmentioning
confidence: 99%
“…[66] For example, Zhang and co-workers developed a transformable nanoparticle for the treatment of triple-negative breast cancer (TNBC) that were formed by the self-assembly of cisplatin, adjudin (ADD), and WKYMVm. [67] Two kinds of peptide-based spherical nanoparticles were designed to deliver Pt and ADD using FFKPt-2TPA-ADDPMGMRGGGG and (2-Nap)-FFKPt-2TPA-ADDPLGVRGGGG. In the two nanoparticles, which had the sequence of (2-Nap)-FFKPt-2TPA-ADDPLGVRGGGG, they can respond to the overexpressed matrix MMP-2 due to the peptide sequence PLGVRG.…”
Section: Chemoimmunotherapymentioning
confidence: 99%